2014
DOI: 10.1590/s1982-56762014000500002
|View full text |Cite
|
Sign up to set email alerts
|

The etiological agent of cotton ramulosis represents a single phylogenetic lineage within the Colletotrichum gloeosporioides species complex

Abstract: Ramulosis of cotton, caused by Colletotrichum gossypii var. cephalosporioides (CGC), is an important disease of cotton in Brazil. The main objective of this work was to test whether CGC is a phylogenetic species inside the Colletotrichum gloeosporioides species complex. A Bayesian inference phylogenetic analysis of a combined ITS and TUB2 dataset was conducted with 21 strains identified as CGC and five strains of Colletotrichum gossypii (CG), associated with cotton anthracnose, obtained from diseased plants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…Although controversy regarding no consistent reports of morphological and molecular markers to differentiate cotton anthracnose and ramulosis fungi exists, 10,11 our study corroborates studies conducted by Silva-Mann et al 9 and Salustiano et al, 12 who used molecular DNA techniques to distinguish successfully CG and CGC fungi. The technique proposed in this work, compared with molecular DNA techniques used to differentiate CG and CGC, is a rapid and low-cost method for accurate identification of these fungi and a non-destructive technique requiring minimal or no sample preparation.…”
Section: 12supporting
confidence: 83%
See 2 more Smart Citations
“…Although controversy regarding no consistent reports of morphological and molecular markers to differentiate cotton anthracnose and ramulosis fungi exists, 10,11 our study corroborates studies conducted by Silva-Mann et al 9 and Salustiano et al, 12 who used molecular DNA techniques to distinguish successfully CG and CGC fungi. The technique proposed in this work, compared with molecular DNA techniques used to differentiate CG and CGC, is a rapid and low-cost method for accurate identification of these fungi and a non-destructive technique requiring minimal or no sample preparation.…”
Section: 12supporting
confidence: 83%
“…Some authors have considered C. gossypii to be a synonym of C. gloeosporioides, but this taxon was not accepted by Sutton. 11 Recently, a molecular phylogenetic analysis conducted by Salustiano et al 12 showed that C. gossypii and C. gossypii var. cephalosporioides formed distinct lineages inside the clade of Colletotrichum theobromicola, a member of the C. gloeosporioides species complex, which allows distinction between the ramulosis and anthracnose pathogens of cotton.…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…Damm et al (2012a, b) and Weir et al (2012) suggested that GAPD H, BTUB2 or glutamine synthetase are among the most effective genes to distinguish single Colletotrichum species that are phylogenetically related. As previously reported (Rodrigues et al 2014;Salustiano et al 2014;Velho et al 2015), multilocus phylogenetic analysis of ITS, GAPDH and BTUB2 allowed for the successful identification of a collection of Colletotrichum spp. obtained from apple.…”
Section: Discussionmentioning
confidence: 52%
“…O gênero é o causador da antracnose da soja (COSTA, 2006), da ramulose (SILVA et al, 2010) e também a antracnose (SALUSTIANO, 2014) em algodão e da antrocnose do colmo e foliar do milho (COÊLHO et al, 2001).…”
Section: Introductionunclassified